Association of resilience with health-related quality of life and depression in multiple myeloma and its precursors: results of a German cross-sectional study. Issue 7 (30th July 2018) - Maatouk, Imad; He, Susanne; Becker, Natalia; Hummel, Manuela; Hemmer, Stefan; Hillengass, Michaela; Goldschmidt, Hartmut; Hartmann, Mechthild; Schellberg, Dieter; Herzog, Wolfgang; Hillengass, Jens
Abstract : Objectives: To investigate the relation between resilience, health-related quality of life (HRQOL) and depression in multiple myeloma (MM) and its premalignant stages. MM is one of the most frequent haematological disorders. It is regularly preceded by asymptomatic stages of the disease namely monoclonal gammopathy of undetermined significance (MGUS) and smouldering multiple myeloma (SMM). Survivors have to cope with mental and physical impairment in terms of HRQOL and depression. The concept of resilience refers to a person's ability to adapt to adversity. Design: Cross-sectional study. Setting: MM outpatient department at a University Hospital in Germany (tertiary care). Participants: 292 consecutive patients from our MM outpatient department. Outcome measures: HRQOL, depression and psychological resilience were assessed with validated questionnaires. Results: Regression analyses were performed to determine associations between resilience, HRQOL and depression. 98 patients (33.6%) had a new diagnosis of active MM, 106 patients (36.3%) were already treated for MM and 88 patients had the diagnosis of a precursor (MGUS or SMM; 30.1%) of MM. Multivariate linear regression analyses revealed a strong positive impact of resilience on physical (b 7.20; 95% CI 4.43 to 9.98; p<0.001) and mental (b 12.12; 95% CI 9.36 to 14.87; p<0.001) HRQOL. Ordered logistic regression analysis showed that the odds for higher depression severity were lowered for individuals with a high level of resilience in comparison to the individuals with a low level of resilience (OR 0.11; 95% CI 0.06 to 0.19; p<0.001). Conclusions: Resilience may be a protective factor in the disease trajectory of MM and its precursors. As a next step, future research should focus on longitudinal assessments at various time points to elucidate the role of resilience in one of the most frequent haematological malignancies.